THE INFLUENCE OF THE USE OF ELETRONIC CIGARETTES ON THE PROGRESSION OF DPOC (CIPEEX, 2025)
Chronic Obstructive Pulmonary Disease (COPD) is a progressive and debilitating respiratory condition, characterized by persistent airflow limitation and chronic airway inflammation. The growing use of electronic cigarettes raises concerns about their impact on disease progression, particularly in individuals already diagnosed or at increased risk of developing COPD. In this context, understanding the effects of electronic cigarettes on lung health becomes essential to support clinical practices and preventive strategies. This study aimed to analyze, through a literature review, the available evidence on the effects of electronic cigarette use on the progression and worsening of Chronic Obstructive Pulmonary Disease (COPD). A literature review was conducted in the PubMed and SciELO databases, using the descriptors Electronic Cigarette and Pulmonary Disease Chronic Obstructive. Articles published in the last six years were included. The analysis of the studies revealed that the potential harmful effects of electronic cigarettes are directly related to their chemical composition. Evidence was identified of cellular injury, airway hyperreactivity, release of inflammatory cytokines (IL-8, IL-10, and TNF), reduction of the antimicrobial action of keratinocytes, and induction of apoptosis in alveolar cells.Although some studies indicate lower exposure to certain toxins compared to conventional cigarettes, others demonstrate that electronic cigarette aerosols contain substances capable of exacerbating airway inflammation, increasing oxidative stress, and impairing lung function in patients with COPD. In the long term, continuous use of these devices may accelerate disease progression. It is concluded that the findings suggest that electronic cigarette use represents an additional risk factor for patients with COPD, potentially aggravating the inflammatory process and accelerating the deterioration of lung function. However, further research is needed to elucidate the specific mechanisms by which electronic cigarettes influence COPD progression and its long-term outcomes.
Keywords: Chronic Obstructive Pulmonary Disease (COPD).; Electronic Cigarette; Pulmonary inflammation